Republic of San Marino : Selected Issues for the 2010 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
This paper examines the development of the business model thus far and considers options for the future. The development of San Marino's financial system over the past two decades is outlined. San Marino's financial sector focuses on services to its residents and the residents of its large neighbor. San Marino's competitiveness is assessed on the basis of real exchange rates. The importance of a strong relationship with Italy may also require San Marino to take more initiatives to amend its position and acquire new skills.